187 Pooled Waiting Lists for Primary Hip and Knee Arthroplasty: Are the Outcomes Inferior to a Named Consultant List?. (28th February 2022) - Thacker, J.; Peake, C.; Balasubramani, P.; Chongbang, T.P.; Jayakanathan, M.; Unnithan, A.
Abstract: Aim: A pooled waiting list model is where patients are treated in turn by the first available surgeon and works to use existing resources more efficiently to better match demand. Aim is to compare quantitative data of patients on the pooled list and named-consultant' list and to determine the superiority of either list based on favourable outcomes. Method: This single centre, retrospective study compared outcomes of primary elective hip and knee arthroplasty for osteoarthritis in patients from pooled and 'named-consultant' waiting lists over a 1-year period. The study period was before the corona virus pandemic. 371 total knee replacements (TKR) and 373 total hip replacements (THR) were included. Baseline characteristics were compared between patients from pooled and named-consultant lists. Results: In the pooled TKR group, a significantly higher proportion of patients were older with higher BMI and ASA grade (p = 0.027, p = 0.479, p<0.001 respectively). There was no difference in baseline characteristics in the THR cohort. Waiting time to surgery was less in the pooled TKR group (mean = 4.17months) with no significant difference in mortality, revision and infection rates, length of stay, operative blood loss, DVT/PE rate, proportion requiring pain team referral and the number with unsatisfactory range of motion at follow-up. There was no significant difference in any outcomes between two groups in the THR cohort. Conclusions: Pooled lists can therefore be an excellent tool in primary THR/TKR to efficiently utilize all available resources (surgeons and theatre time) without compromising on patient outcomes and prompting use in all UK arthroplasty centres.